Effects of different cooking methods on volatile flavor compounds, nutritional constituents, and antioxidant activities of Clitocybe squamulosa - Yuan, Hui; Xu, Lijing; Chang, Mingchang; Meng, Junlong; Feng, Cuiping; Geng, Xueran; Cheng, Yanfen; Liu, Zongqi (Frontiers in Nutrition, 2022)
To explore a scientific and reasonable cooking method for Clitocybe squamulosa, four cooking methods (boiling, steaming, microwaving, and frying) were applied to C. squamulosa, and the effects of different cooking methods on volatile flavor compounds, nutritional constituents, and antioxidant activities in C. squamulosa were systematically investigated. The results showed that 54, 53, 61, 63, and 49 volatile flavor compounds were detected in raw, boiled, steamed, microwaved, and fried samples, respectively. Large differences in volatile flavor compounds between the four cooking and raw samples were determined by using relative odor activity values (ROAV) and principal component analysis (PCA). In addition, steaming and microwaving could protect the nutrients of C. squamulosa, reduce losses during the cooking process and improve the color of cooked products compared to boiling and frying cooking methods. Meanwhile, cooking treatment exerted different effects on the antioxidant activity of C. squamulosa, and the antioxidant activity of C. squamulosa was the highest after microwave cooking treatment. This research can provide a theoretical basis for the cooking, processing and utilization of C. squamulosa and other wild edible fungi.